Tren pemanfaatan teknologi Augmented Reality (AR) dalam sektor pendidikan: Analisis peluang dan hambatan implementasi - Ardhi, Muhammad Ali nur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the trend of Augmented Reality (AR) utilization in the education sector and to identify its opportunities and implementation challenges. The research employs a literature review method by examining various academic sources, industry reports, and case studies related to AR applications in educational contexts. The findings indicate that AR has significant potential to enhance learning quality through the visualization of abstract concepts, high interactivity, and more engaging and immersive learning experiences. This technology can improve students’ motivation, engagement, and understanding, while also supporting more personalized and efficient learning processes. However, the implementation of AR still faces several challenges, including limited infrastructure, digital divide, high costs, and lack of teacher readiness and competence. In addition, integrating AR into existing curricula remains a critical issue. Therefore, collaborative strategies involving governments, educational institutions, and technology developers are necessary to optimize AR adoption. This study concludes that AR is a crucial innovation with the potential to transform education in the digital era.